1988
DOI: 10.1002/ajim.4700140205
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Carbide in Lung Tissue of a Worker in the Abrasive Industry

Abstract: Lung tissue of a worker in an abrasive manufacturing plant, whose duration of dust exposure was about 10 years, was analyzed by means of bulk analysis and in situ analytical electron microanalysis. The content of the total dust in the lung was 120 mg/g of the dried lung tissue. This value is close to the average concentration of the total dust in the lungs of coal miners with massive fibrosis. The lung dust composition in this case was approximately 43% silicon carbide, 24% aluminium oxide, 2.3% cristobalite, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In experimental studies (10-13), SIC fibers have shown a high carcinogenic potency and a long durability in human lung tissue, suggesting that they may be a plausible cause of the observed excess of lung cancer (15,16). In the present study, the analysis in which both quartz exposure and SiC fiber exposure were included showed some empirical evidence that the latter is a better indicator of lung cancer risk than is crystalline silica (table 6).…”
Section: Lung Cancersupporting
confidence: 52%
See 1 more Smart Citation
“…In experimental studies (10-13), SIC fibers have shown a high carcinogenic potency and a long durability in human lung tissue, suggesting that they may be a plausible cause of the observed excess of lung cancer (15,16). In the present study, the analysis in which both quartz exposure and SiC fiber exposure were included showed some empirical evidence that the latter is a better indicator of lung cancer risk than is crystalline silica (table 6).…”
Section: Lung Cancersupporting
confidence: 52%
“…Substantial interest has been focused on SiC fibers or SiC whiskers, which, in experimental studies, have been shown to have carcinogenic and fibrogenic properties comparable to those of asbestos (10)(11)(12)(13). The finding of SiC fibers in the work environment of SiC smelters (1,9,14) and in the lung tissue of workers in that industry (15,16) has suggested the presence of a possible, unrecognized hazard.…”
mentioning
confidence: 99%
“…Silicon Carbide whisker (SiCW) is produced by the heating of rice hulls in a reducing atmosphere. Although isogeometric SiC was generally considered no worse than a "nuisance dust", evidences appeared that workers exposed during the manufacturing process might suffer chronic lung damage [1][2][3] . The advent of controlled SiCW manufacture and industrial use is much more recent and no epidemiological information is yet available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A health risk among SiC workers has been noticed since the beginning of the 19 th century (Winslow et al, 1919;Bruusgaard, 1948). Occupational analyses focusing on the Acheson process showed that the airborne environment was charged with SiC microparticles, SiC fibers and impurities, especially crystalline silica and carbon (Hayashi and Kajita, 1988;Osterman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, analyses of lung tissue biopsies from workers exposed to these powders have revealed substantial amounts of SiC particles in alveolar spaces and interstitial fibrosis associated with an increased pneumoconiosis incidence (Funahashi et al, 1984;Hayashi and Kajita, 1988;MassĂ© et al, 1988;Dufresne et al, 1992). Taken together, these observations were considered to be the result of a silicogenic (fibrogenic) effect (Bruch et al, 1993b) and showed the importance of occupational risk evaluation on SiC exposure, through toxicological studies (Bruch et al, 1993a(Bruch et al, , 1993bBruch and Rehn, 1996).…”
Section: Introductionmentioning
confidence: 99%